Giant pandas - Herrington, Lisa M. (2019)
Did you know that a giant panda eats more than 600 bamboo stems a day-but that it doesn't stop these bears from being expert tree climbers? This title offers a complete picture of the animal- from birth to adulthood- and describes its place in our world, including how humans impact it and its environment.
Includes index.
8-11
Keywords: Giant panda -- Juvenile literature